Early Impact of the Affordable Care Act and Medicaid Expansion on Racial and Socioeconomic Disparities in Cancer Care. (March 2020) - Mahal, Amandeep R.; Chavez, Janice; Yang, David D.; Kim, Daniel W.; Cole, Alexander P.; Hu, Jim C.; Trinh, Quoc-Dien; Yu, James B.; Nguyen, Paul L.; Mahal, Brandon A.
Abstract : Objectives: We sought to evaluate sociodemographic disparities in insurance coverage among nonelderly adults with a common cancer after Affordable Care Act (ACA) implementation. Patients and Methods: In total, 109, 182 patients aged 18 to 64 years diagnosed with a common cancer (lung, breast, or prostate cancer) were identified from 2010 to 2014. Multivariable logistic regressions analyzed associations between ACA implementation and uninsured rates on the basis of state approach to Medicaid expansion, stratified by race (black, white), and income (stratified at 138% Federal Poverty Line). Results: Uninsured rates declined after ACA implementation, with the greatest rate reductions associated with traditional Medicaid expansion ( P interaction <0.001). Racial disparities in insurance coverage were eliminated with traditional Medicaid expansion where the uninsured rate went from 10.0% to 0.95% among black patients (adjusted odds ratio [AOR]pre-aca 1.52 to AORpost-aca 0.47) but persisted with other state approaches (AORpre-aca 1.15 to AORpost-aca 1.12) ( P interaction =0.002). Furthermore, socioeconomic coverage gaps were eliminated with traditional Medicaid expansion, where the uninsured rate went from 8.4% to 1.4% among low-income (⩽138% Federal Poverty Line) patients, but not with other state approaches ( P interaction <0.001). Conclusions: Traditional Medicaid expansion was associated with the elimination of racial and socioeconomic insurance coverage gaps. These results highlight the potential benefits and challenges of the ACA and its provisions, and could instruct ongoing policy.